PORNOGRAFI DAN PORNOAKSI (Perspektif Sejarah dan Hukum Islam) - yandi maryandi (Prodi Hukum Keluarga Islam (Ahwal Asy-Syakhsiyyah) Fakultas Syariah Unisba, 2018)
Abstrak: Pornography and pornoaction happen because of modernization and globalization influence on sosiety lives. Without consciousness from society to solve the above problems which considering Islamic community public interest, pornography and pornoaction always emerge. Islam as doctrine early presents to solve the problems, so there are many Quranic verses and prophet traditions regulate the dress, communication between man and woman, including the publications that appear moral decadence.Kata kunci: pornografi, pornoaksi, Islam.